Repeated burning undermines the value of regenerating cattle pastures for tropical forest birds. (July 2022) - Lello-Smith, Anna; Rodewald, Amanda D.; Ramos, Victor Hugo; Rosenberg, Kenneth V.; Ruiz-Gutierrez, Viviana
Abstract: Forest restoration has become a central strategy to conserve biodiversity, especially in the global tropics, but many priority regions are increasingly threatened by anthropogenic stressors. Of particular concern is the growing frequency of fire in humid tropical systems due to agricultural expansion and regional drying. Yet little is known about how fire affects recovery of tropical biodiversity in restored lands, including forest-dependent and threatened species. Here we provide the first assessment of the impacts of burning within naturally regenerating cattle pastures on pasture use by Neotropical forest birds. Working within 1–11-year-old regenerating pastures in Guatemala's Maya Biosphere Reserve, we asked how occupancy rates of forest-dependent and threatened bird species differ between repeatedly burned and unburned pasture. To better understand the effect of fire on pasture use, we examined how species' opportunistic use of regenerating pastures is a function of vegetation succession at local scales. We found that 70 forest-dependent and 19 threatened species used unburned pastures, but fire reduced or eliminated pasture use for 56% of forest-dependent and 53% of threatened species. Local vegetation succession explained the likelihood of colonizing pastures for nearly half of forest species that used regenerating pastures. Species closely associated with closed-canopy vegetation were most likely to be partially or fully excluded from burned pasture, suggesting that fire excluded certain species by impeding forest regrowth. Our results clearly demonstrate that burning undermines the high value of regenerating pastures for forest-dependent and threatened species and highlight the critical importance of preventing human-caused fires in restored tropical landscapes.